A Polymorphism Within the Connective Tissue Growth Factor (CTGF) Gene has No Effect on Non-Invasive Markers of Beta-Cell Area and Risk of Type 2 Diabetes. Issue 4 (27th May 2013) - Pivovarova, Olga; Fisher, Eva; Dudziak, Katarzyna; Ilkavets, Iryna; Dooley, Steven; Slominsky, Petr; Limborska, Svetlana; Weickert, Martin O.; Spranger, Joachim; Fritsche, Andreas; Boeing, Heiner; Pfeiffer, Andreas F. H.; et al.
Abstract : Chromosomal locus 6q23 is strongly linked to type 2 diabetes (T2DM) and related features including insulin secretion in various ethnic populations. Connective tissue growth factor (CTGF) gene is an interesting T2DM candidate gene in this chromosome region. CTGF is a key mediator of progressive pancreatic fibrosis up-regulated in type 2 diabetes. In contrast, CTGF inactivation in mice compromises islet cell proliferation during embryogenesis. The aim of our study was to investigate an impact of CTGF genetic variation on pancreatic beta-cell function and T2DM pathogenesis. We studied the effect of a common CTGF polymorphism rs9493150 on the risk of the T2DM development in three independent German cohorts. Specifically, the association between CTGF polymorphism and non-invasive markers of beta-cell area derived from oral glucose tolerance test was studied in subjects without diabetes. Neither in the Metabolic Syndrome Berlin Potsdam (MESYBEPO) study ( n = 1026) (OR = 0.637, CI (0.387–1.050); p = 0.077) nor in the European Prospective Investigation into Cancer and Nutrition-Potsdam (EPIC-Potsdam) ( n = 3049) cohort (RR = 0.77 CI (0.49–1.20), p = 0.249 for the recessive homozygote in general model), a significant association with increased diabetes risk was observed. The risk allele of rs9493150 had also no effect on markers of beta-cell area in the combined analysis of the MESYBEPO and Tübingen Family Study ( n = 1826). In conclusion, the polymorphism rs9493150 in the 5'-untranslated region of the CTGF gene has no association with T2DM risk and surrogate markers of beta-cell area.